Graphene oxide/ε-poly-L-lysine self-assembled functionalized coatings improve the biocompatibility and antibacterial properties of titanium implants - You, Xiaoxiao; Wang, Zhongke; Wang, Li; Liu, Youbo; Chen, Hongmei; Lan, Xiaorong; Guo, Ling (Frontiers in Bioengineering and Biotechnology, 2024)
The construction of an antibacterial biological coating on titanium surface plays an important role in the long-term stability of oral implant restoration. Graphene oxide (GO) has been widely studied because of its excellent antibacterial properties and osteogenic activity. However, striking a balance between its biological toxicity and antibacterial properties remains a significant challenge with GO. ε-poly-L-lysine (PLL) has broad-spectrum antibacterial activity and ultra-high safety performance. Using Layer-by-layer self-assembly technology (LBL), different layers of PLL/GO coatings and GO self-assembly coatings were assembled on the surface of titanium sheet. The materials were characterized using scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and contact angle test. The antibacterial properties of Porphyromonas gingivalis (P.g.) were analyzed through SEM, coated plate experiment, and inhibition zone experiment. CCK-8 was used to determine the cytotoxicity of the material to MC3T3 cells, and zebrafish larvae and embryos were used to determine the developmental toxicity and inflammatory effects of the material. The results show that the combined assembly of 20 layers of GO and PLL exhibits good antibacterial properties and no biological toxicity, suggesting a potential application for a titanium-based implant modification scheme.